2004
DOI: 10.1007/s00134-004-2160-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of older patients receiving mechanical ventilation

Abstract: Older mechanically ventilated patients (age >70 years) had a lower ICU and hospital survival, but the duration of mechanical ventilation, ICU and hospital stay were similar to younger patients. Factors associated with the highest risk of mortality in patients older than 70 were the development of complications during the course of mechanical ventilation, such as acute renal failure and shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 22 publications
2
48
1
13
Order By: Relevance
“…We excluded studies published before 2001 because the practice of critical care and critical care outcomes has changed considerably since that time. 6,7 We also searched several other sources: we reviewed the reference lists of selected studies, we contacted experts in the fi eld to identify missed or unpublished studies, and we performed a manual examination of abstracts books from the main international meetings of critical care medicine (International Symposium on Intensive Care and Emergency Medicine, European Society Intensive Care Medicine Meeting, Society of Critical Care Medicine) between 2007 and 2014 to locate additional relevant titles. For studies published in abstract form, the primary author was contacted to identify manuscripts in progress.…”
Section: Search Methodsmentioning
confidence: 99%
“…We excluded studies published before 2001 because the practice of critical care and critical care outcomes has changed considerably since that time. 6,7 We also searched several other sources: we reviewed the reference lists of selected studies, we contacted experts in the fi eld to identify missed or unpublished studies, and we performed a manual examination of abstracts books from the main international meetings of critical care medicine (International Symposium on Intensive Care and Emergency Medicine, European Society Intensive Care Medicine Meeting, Society of Critical Care Medicine) between 2007 and 2014 to locate additional relevant titles. For studies published in abstract form, the primary author was contacted to identify manuscripts in progress.…”
Section: Search Methodsmentioning
confidence: 99%
“…Also in the presence of acute kidney injury (AKI) most studies have documented that advanced age is independently associated with increase hospital mortality [12]. Mechanical ventilation, both invasive and noninvasive, is also associated with increased mortality in the elderly compared with younger age groups [13,14]. Studies of sepsis have shown an exponential increase in the population-based incidence of sepsis with age, followed closely by an increased mortality.…”
Section: Mortalitymentioning
confidence: 99%
“…Older adults may be at greater risk for nosocomial infections and subsequent mortality compared with younger patients (29), although there is some evidence that older adults may be less likely to develop ventilator-associated pneumonia (30). Simple evidence-based interventions that can reduce rates of catheterrelated bloodstream infections (31) and ventilator-associated pneumonia (32) remain underused in the ICU setting.…”
Section: Nosocomial Infectionsmentioning
confidence: 99%